The use of antibiotic prophylaxis in patients undergoing urologic procedures in an academic hospital Surabaya: A retrospective study - Tri Pudy Asmarawati; Tarmono Djojodimedjo; Dimas Panca Andhika; Musofa Rusli; Mariyatul Qibtiyah; Bagus Aulia Mahdi; Dwiki Novendrianto; Okla Sekar Martani; Hari Paraton; Heiman Wertheim; Kuntaman Kuntaman (Journal of Infection in Developing Countries)
Introduction: Prophylactic antibiotics in urological procedures are essential to prevent postoperative infections. A different approach in selecting antibiotic prophylaxis according to the type of procedure is needed.